2017
DOI: 10.1063/1.4974682
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Dodd and Deeds solutions for a transmit-receive eddy current probe above a layered planar structure

Abstract: Abstract. Exact solutions for the electromagnetic response of a transmit-receive coil pair situated above two parallel plates separated by a gap, were developed using the recently published general model of Desjardins et al. that accounts for all electromagnetic interactions between the voltage-driven probe and the conducting samples. This model was then compared to the well-known model developed by Dodd and Deeds, which assumes a constant amplitude sinusoidal current and an open-circuit pick-up coil. Both mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Luloff et al examined Desjardins et al 's model of a non-coaxial sensor probe above two separated sample plates by utilizing the Dodd-Deeds model. It was found that both methods are matched with the experiments under the low frequency [19]. In [20], by combining the analytical solution and FEM simulations, the ferrite fraction can be inferred with the error typically less than 8 %.…”
Section: Introductionmentioning
confidence: 68%
“…Luloff et al examined Desjardins et al 's model of a non-coaxial sensor probe above two separated sample plates by utilizing the Dodd-Deeds model. It was found that both methods are matched with the experiments under the low frequency [19]. In [20], by combining the analytical solution and FEM simulations, the ferrite fraction can be inferred with the error typically less than 8 %.…”
Section: Introductionmentioning
confidence: 68%
“…In recent years, the Dodd-Deeds formula [31] has been widely used for the inductance analysis of the air-core coil above the conductive plates [32]- [37]. For the designed eddy current sensor shown in Fig.…”
Section: Material-independent Algorithm and LII Feature A Original Analytical Formulationmentioning
confidence: 99%
“…Parameters, including the inversed liftoff distance, LII L 0 , and its corresponded frequency, are used for the inversion of the relative magnetic permeability of the steel using iterative equations from (30) to (32). In Fig.…”
Section: Inversion Of Magnetic Permeability Based On the Feature LIImentioning
confidence: 99%
“…α and α 1 are related to the wavenumber of the EM plane wave of Transverse electric (TE) mode [17] in the free space and test piece, respectively. α = √ 2 + 2 (5) (3) and h( , )e j( r + ) in (4) are the Fourier transform of the free-space magnetic scalar potential generated by the driving transmitter and pick-up receiver respectively, with h( , ) defined as the following expression.…”
Section: A Original Formulas Of Thin-skin Regime -Mutual-impedance Omentioning
confidence: 99%